Alternatives for non-verbal and minimally verbal autism communication (Research, Society and Development, 2024)
Objective: To present alternatives for communication for non-verbal and minimally verbal autistic people. Method: An integrative review of the literature was carried out, between the months of June and November of the year 2023, using the health science descriptors “Autism Spectrum Disorder”, “Nonverbal Communication”, “Child” and “Human Development”, through the Scielo, VHL and PubMed databases. Results and Discussions: Good communication, through words early in life, suggests greater expressive development in the child with ASD in the long term. Strategies such as the Naturalistic Developmental Behavioral Intervention (NDBI) and Toy Talk were used during recreational moments for children with ASD, through these methods it was possible to demonstrate an increase in the exposure of autistic children to a greater number of sentences pronounced. In relation to other intervention mechanisms, the results demonstrated that this instrument was fundamental for the significant non-verbal progress of these patients, as it presented a greater positive variable, when compared to the others. PECS-Adapted can also be an option, as it allows the expansion of communicative intention and other participatory skills, enabling functional communication. Furthermore, robots have also been used to optimize the communication of autistic children, as these individuals interact more effectively with robots than with humans. Final Considerations: It is essential to stimulate and promote the development of these children's language of expression, through strategies that use everyday, playful activities, direct participation of parents or health professionals, in addition to the use of new technologies.